CGIAR Advisory Services: 2020 Narrative and Financial Report - CGIAR Advisory Services Shared Secretariat (CGIAR Advisory Services, 2021)
2020 marked an eventful year across CGIAR. Advisory Services’ work furthers the System’s effectiveness, its culture of continual learning, and its transition to One CGIAR. Read our summary 2020 technical and financial report.